Application of Computer Aided Process Planning in Manufacturing Industries - Atnaw, Samson M.; Kulkarni, R. R. (Penerbit Universiti Malaysia Pahang, 2015)
In today’s economy, products and processes tend to increase in complexity of design and functionality. Furthermore, they are in need of high-sophisticated manufacturing and assembly processes. On the other hand, increasing competition results in the demand for shorter product life cycles and forces companies of cut down development and delivery times. Thus, modern manufacturing has to adapt to new requirements of this dynamic environment. In this context, innovative information technologies in general and flexible as well as adaptive concepts for process planning and production control in particular are of increasing importance for business success. Among the whole manufacturing cycle of a product, a sequence of manufacturing stages needs to be optimized using the increasingly available computing resources. Computer aided process planning is seen as the missing link between CAD and CAM, which relates to the translation of design tolerances into manufacturing tolerances to be executed in the shop floor. In this paper, the general topic of process planning, the implementation and theoretical foundation of CAPP, the role of CAPP in concurrent engineering (CE), various classifications of CAPP systems and its application in job shop type of industries is presented.